PETROLEUM PRODUCTS DISTRIBUTION AND CABOTAGE POLICY IMPLEMENTATION CHALLENGES IN NIGERIA - ADEPOJU, O. O.; BELLO. K.; OGOLA, D. B. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE RESEARCH AND ANTHROPOLOGY, 2023)
This study was to examine reasons Cabotage enactment of 2004 has not been fully implemented in Nigeria. Secondly, is to analyse the pattern of petroleum distribution Petroleum Motor Spirit (PMS) across Nigerian states. 279 persons from major shipping companies involved in carriage of crude oil were sampled and the Inland and Coaster shipping Act was carefully read to understand grey areas in the policy. Quarterly Petroleum Motor Spirit (PMS) distributions from 2016 to 2019 were collected from National Bureau of Statistics website and the trend of forecast was predicted by a regression analytical technique. Descriptive analysis has been used to explain the non-fully implementation of Cabotage Act based on responses received. Quarterly data shows that, Lagos, Kano, Niger, Ogun, Oyo states were at the fore front of PMS demand in Nigeria. Results from the findings revealed that, it is very difficult for Cabotage to be fully implemented in Nigeria. Factors responsible for inability to be fully implemented are related to weak policy enforcement, lack political will, Cabotage Vessel Financing Fund (CVFF), seaworthiness of vessels, joint ventures and waivers respectively. The research concluded that, the issues of FOB and CIF can be resolved with the use of political will by implementing capacity building through CVFF and removal of waivers in the Cabotage Act. PMS distribution has shown a correlation between the demand for the PMS and population of the states.
This study was to examine reasons Cabotage enactment of 2004 has not been fully implemented in Nigeria. Secondly, is to analyse the pattern of petroleum distribution Petroleum Motor Spirit (PMS) across Nigerian states
Keywords: petroleum; distribution; cabotage and Nigeria; Motor Spirit Cabotage